Optimized Decoding-Energy-Aware Encoding In Practical VVC Implementations - Kranzler, Matthias; Wieckowski, Adam; Ramasubbu, Geetha; Bross, Benjamin; Kaup, Andre; Marpe, Detlev; Herglotz, Christian (Proceedings - International Conference on Image Processing, 2022)
The optimization of the energy demand is crucial for modern video codecs. Previous studies show that the energy demand of VVC decoders can be improved by more than 50% if specific coding tools are disabled in the encoder. However, those approaches increase the bit rate by over 20% if the concept is applied to practical encoder implementations such as VVenC. Therefore, in this work, we investigate VVenC and study possibilities to reduce the additional bit rate, while still achieving low-energy decoding at reasonable encoding times. We show that encoding using our proposed coding tool profiles, the decoding energy efficiency is improved by over 25% with a bit rate increase of less than 5% with respect to standard encoding. Furthermore, we propose a second coding tool profile targeting maximum energy savings, which achieves 34% of energy savings at bitrate increases below 15%.